Phycoremediation potential of microalgae species for ethidium bromide removal from aqueous media. Issue 11 (18th September 2020) - de Almeida, Heleno Cavalcante; Salomão, André Luís de Sá; Lambert, Janaina; Teixeira, Lia Cardoso Rocha Saraiva; Marques, Marcia
Abstract: Ethidium Bromide (EtBr) is an organic compound used in molecular biology investigations. EtBr ability of intercalating in the DNA molecule makes it a toxic substance. The objective was to evaluate the phycoremediation potentials of Chlorella vulgaris, Desmodesmus subspicatus and Raphidocelis subcapitata tested separately and in a mixture (Mix) for EtBr removal from the aqueous medium. Experiments were conducted using an initial algae biomass of 10 6 cell/mL, exposed to 500 µg/L of EtBr. The removal efficiency (µg EtBr L −1 ) after 3 h in each treatment were: Mix (72.8 µg.L −1 ) > D. subspicatus (48.4 µg.L −1 ) > R. subcapitata (24.6 µg.L −1 ) > C. vulgaris (19.9 µg.L −1 ). However, when EtBr mass reduction per microalgae density is considered (ng.algae −1 ), the efficiency ranking changes to: D. subspicatus (1.9 × 10 −5  ng.algae −1 ) > C. vulgaris (1.4 × 10 −5  ng.algae −1 ) >Mix (9.8 × 10 −6  ng.algae −1 ) > R. subcapitata (2.8 × 10 −6  ng.algae −1 ). The results suggest that initial algal population density is a determinant factor for efficient EtBr removal by microalgae species in short term treatments. In order to obtain 100% of EtBr removal, it should be necessary 10 10, 10 10 and 10 11 algae.mL −1 of C. vulgaris, D. subspicatus and R. subcapitata, respectively. The results strongly suggest phycoremediation can be explored as an alternative method for EtBr removal.